An Empirical Study on SaaS Adoption Among SMEs in India - Gurav, Vijay V (Digital Repository of Theses - SSBM Geneva, 2024)
This study investigates the factors influencing the adoption of Software as a Service (SaaS) among small and medium-sized enterprises (SMEs) by integrating UTAUT & TTAT theories. The research collected data from 900 respondents across various regions in India. Partial Least Squares Structural Equation Modelling (PLS-SEM) is used in the analysis to evaluate the associations between the intention to use SaaS, perceived danger, social influence, effort expectancy, and enabling factors. Key findings reveal that effort expectancy, facilitating conditions, and social influence positively impact the intention to adopt SaaS, emphasizing the importance of user-friendly interfaces, robust support, and endorsements from industry leaders. Conversely, perceived threat, including perceived severity and susceptibility, significantly deters adoption, highlighting the need for stringent security measures and transparent communication to mitigate risks. Performance expectancy also contributes positively but moderately to the intention to use SaaS, underscoring the perceived performance benefits. The Importance-Performance Map Analysis (IPMA) further elucidates these factors, suggesting targeted strategies to enhance SaaS adoption. Recommendations include focusing on intuitive design, providing comprehensive support, addressing security concerns, leveraging social influence, and clearly communicating performance benefits. By adopting a holistic approach, SaaS providers can better meet the needs of SMEs, driving broader adoption and supporting technological advancement and operational efficiency in the SME sector. This study's implications offer valuable insights for SaaS providers, policymakers, and SMEs, highlighting the critical factors and practical strategies to promote the adoption of SaaS solutions, ultimately contributing to the competitiveness and resilience of SMEs in the evolving business landscape. Keywords: SaaS adoption, SMEs, UTAUT, TTAT, PLS-SEM.